How Fit Are Special Operations Police Officers? A Comparison With Elite Athletes From Olympic Disciplines - Lukas Zwingmann (Frontiers Media S.A., 2021)
The diverse tasks of special operations police (SOP) units place high physical demands on every officer. Being fit for duty requires a wide range of motor abilities which must be trained regularly and in a structured manner. But SOP operators have to plan and manage large proportions of their training alone, which makes it difficult to control. Therefore, this study aimed to highlight strengths and deficits of the SOP operators' fitness by comparing them to elite athletes, and to define future training goals. Retrospective data of 189 male SOP operators were used, who completed several isometric strength tests, a graded exercise test to determine maximal oxygen uptake, and countermovement jumps to determine leg muscle power. On the basis of a literature search, performance data were then compared to a total of 3,028 elite male athletes from 36 Summer Olympic disciplines. Pooled means and standard deviations were calculated for each discipline and effect sizes were used to analyze their similarities and differences to the SOP unit. On average, SOP operators were taller, heavier, and stronger than elite athletes. But both the ability to convert this strength into explosive movement and aerobic power was significantly less developed. From this point of view, SOP operators should consider polarized endurance training to work efficiently on improving aerobic performance. In addition, regular plyometric training seems necessary to improve leg muscle power and agility.